A pedagogia do Grupo Casadão : fruto e semente da luta pela terra no Baixo Araguaia Mato-grossense - Silva, Solange Pereira da (2015)
This study aims to understand what bonds give support to Casadão Group, how they were built, and what makes them subject of the pedagogical collective in the land dispute in Araguaia. By recording the accounts through interviews held with the main individuals engaged in this Group, meanings accredited to reality in which they are immersed and to the effective daily practices were possible to be apprehended. Ten people were chosen taking into account their relevance to the outlining and sedimentation of the theoretical and methodological referential that grounds the Group pedagogy. Apart from the interviews, bibliographical research, research in official and local non-governmental organizations documents, and field journal were carried out, as well as visits to fields. Results of the study indicate that pressure brought to bear for the advance of agro-exporters in Araguian region, the lack of infrastructure in the settlements, besides the inexistence of social and economical policies to value local social-biodiversity go on laying the population open to social and political vulnerabilities. Results also show, contrary to this situation, that organizations tied up to popular social movements pursue ways to engage peasant families and start educational processes to awaken and to organize their collective will, considering forging a societal plan, a new hegemony. In the course of daily life, as a feedback, these subjects have combined their struggle, organization, faith, art and work to restore the meaning of the relationships that are defined in themselves and along with political and economical forces, in order to recreate a societal plan that provides them with land, territory, work and dignity, based on the defense of the collective natural assets and social justice. Such an outcome allows us to conclude that Casadão Group has effectively become a pedagogical subject, creator of a collective will and a new culture that recognizes social, political, economical, spiritual, artistic and affective dimensions. In itself, it is able to provide through collective work, perspective of the symbiotic relation with nature. Mutually, its land dispute feeds the struggle for the planet Earth.